2015
DOI: 10.3174/ajnr.a4571
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Psoas Sign in Lumbar Spinal Infections: Evaluation of Diagnostic Accuracy and Comparison with Established Imaging Characteristics

Abstract: BACKGROUND AND PURPOSE:Lumbar discitis-osteomyelitis has imaging characteristics than can overlap with noninfectious causes of back pain. Our aim was to determine the added accuracy of psoas musculature T2 hyperintensity (imaging psoas sign) in the MR imaging diagnosis of lumbar discitis-osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Owing to its high sensitivity and specificity of up to 90% or greater [15], it is a powerful diagnostic tool in the early diagnosis of spondylodiscitis. MR imaging thus provides help in prompt initiation of appropriate therapy which may be medical or surgical, by defining the extent of involvement and detection of complications such as epidural and paraspinal abscesses.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high sensitivity and specificity of up to 90% or greater [15], it is a powerful diagnostic tool in the early diagnosis of spondylodiscitis. MR imaging thus provides help in prompt initiation of appropriate therapy which may be medical or surgical, by defining the extent of involvement and detection of complications such as epidural and paraspinal abscesses.…”
Section: Introductionmentioning
confidence: 99%
“…We propose that MRI signal changes, as STIR or T2-weighted hyperintensity, of the LCM without calcification of the tendon could represent a potentially important sign suggestive of pyogenic inflammation in cervical spinal infections, including cervical discitis-osteomyelitis. Ledbetter et al recently reported that psoas T2 hyperintensity, as the imaging psoas sign, correlates closely with discitis-osteomyelitis [ 7 ]. LCM hyperintensity without tendon calcification in the cervical region might have diagnostic value similar to psoas T2 hyperintensity in the lumbar region.…”
Section: Discussionmentioning
confidence: 99%
“…There are no reports specifically addressing the question of whether a 1.5 Tesla magnet is the minimum required for the diagnosis of SD. However, the vast majority of authors of published papers performed MRI using 1.5 T or higher magnet [55,110,161,162].…”
Section: Level Of Evidence:mentioning
confidence: 99%